Navigating family involvement in domestic violence fatality review: conceptualising prospects for systems and relational repair - Rowlands, James (Journal of family violence, 2022)
Purpose: Family involvement is a key element of Domestic Homicide Review (DHR), the form of Domestic Violence Fatality Review (DVFR) found in England and Wales. Family involvement is framed as having dual purposes: first, as a benefit to DHRs, enabling a fuller picture of victims’ experiences; second, as a benefit to families themselves, notably as a therapeutic or cathartic opportunity. However, these dual purposes have been little considered. This conceptual article responds to this absence by interrogating the purpose, process and outcomes of family involvement within DHRs. Method: To explicate purpose, process and outcomes, we synthesise policy, practice and the extant empirical and theoretical literature relating to family involvement in DHRs. We supplement this by engaging with a broader body of emerging research on family involvement in other review systems, analysing this through a lens of citizenship and participation. Results: Family involvement in DHRs is little explicated and there is a need to better engage with how family are involved in DHRs, as a way of increasing transparency for family rights. By way of response, a tentative conceptual framework is proposed which situates family involvement as demonstrative of systems- and relational-repair. Conclusions: The article concludes by arguing for greater attention to the Theory(s) of Change underpinning both the place of the family and their testimony, as well as the DHR system as a whole. Such clarity would benefit family, both as the subject of professional interactions but, critically, as agents in the DHR process in their own right.